Fundamentals of Translational Neuroscience in Toxicologic Pathology: Optimizing the Value of Animal Data for Human Risk Assessment. (January 2015) - Morrison, James P.; Sharma, Alok K.; Rao, Deepa; Pardo, Ingrid D.; Garman, Robert H.; Kaufmann, Wolfgang; Bolon, Brad
A half-day Society of Toxicologic Pathology continuing education course on "Fundamentals of Translational Neuroscience in Toxicologic Pathology" presented some current major issues faced when extrapolating animal data regarding potential neurological consequences to assess potential human outcomes. Two talks reviewed functional–structural correlates in rodent and nonrodent mammalian brains needed to predict behavioral consequences of morphologic changes in discrete neural cell populations. The third lecture described practical steps for ensuring that specimens from rodent developmental neurotoxicity tests will be processed correctly to produce highly homologous sections. The fourth talk detailed demographic factors (e.g., species, strain, sex, and age); physiological traits (body composition, brain circulation, pharmacokinetic/pharmacodynamic patterns, etc.); and husbandry influences (e.g., group housing) known to alter the effects of neuroactive agents. The last presentation discussed the appearance, unknown functional effects, and potential relevance to humans of polyethylene glycol (PEG)–associated vacuoles within the choroid plexus epithelium of animals. Speakers provided real-world examples of challenges with data extrapolation among species or with study design considerations that may impact the interpretability of results. Translational neuroscience will be bolstered in the future as less invasive and/or more quantitative techniques are devised for linking overt functional deficits to subtle anatomic and chemical lesions.